Fiscal Decentralisation and Deficits: International Evidence - Bilin Neyapti (Turkish Economic Association, 2003)
The literature on socio economic implications of fiscal decentralization (FD) has recently been expanding, though only very few studies to day have looked at its macroeconomic effects. This paper investigates the relationship between FD and budget deficits. Using various measures of both expenditure and revenue decentralization in a large panel data set, we show that FD is significantly and negatively related to budget deficits. Moreover, among the many possible factors that may reinforce this relationship, country size is the most relevant one. The paper also presents significant evidence that, the larger the country size, both good governance and local accountability accentuates the relationship between FD and budget deficits.
Keywords: E62; H62; H71; H72; 330; Fiscal Decentralization; Budget Deficits